HOUSE'S SOLAR CHIMNEY A NUMERICAL ANALYSIS ON THE THERMAL PERFORMANCE IN JAKARTA - Bachrun, Abraham Seno; Vidiyanti, Christy; Ismail, Lokman Hakim; Abd. Wahab, Izudinshah (SINERGI, 2020)
The abundance of solar light in tropical countries is the advantage of the utilization of solar energy. Increasingly expensive electricity forces buildings to use passive ventilation as building coolers. One of them is the use of the stack effect through the solar chimney. The absence of residential buildings that use the solar chimney as part of a passive ventilation system makes the need for prototypes for residential buildings. The application of solar chimney to homes in Jakarta is something new. Six types of the solar chimney have been tested on a prototype, one-story residential houses in Jakarta. The location was assumed to be in the densely populated area of South Jakarta. Wind velocity ambient data using Rubber locations. Using Ansys 16.0, simulations have been carried out, and solar chimney with double-full roof collector was able to induce a wind velocity of 0.41 m/s on average